can u help me obtain the general equation of this

(( xcsc (y/x) - y ))dx + xdy = 0

September 14, 2017 - 7:48am

#1
Homogeneous equations- general solution

September 14, 2017 - 7:48am

#1
shaaarmiii

Homogeneous equations- general solution

can u help me obtain the general equation of this

(( xcsc (y/x) - y ))dx + xdy = 0

Subscribe to MATHalino.com on

We're now on YouTube! Please subscribe.

- Decimal Fractional Parts of Segment Dim's on Hypotenuses of Dissimilar Right Triangles
- Family of Plane Curves
- Acceleration of Riged body (flyweight) with forces
- Cables and Arches
- Trigo sin cos tan sec csc cot
- Arithmetic sequence
- Round off 314.587321 into four significant figures
- algebra 1
- Concavity calculus
- Problem 126 explanation please

- Family of Plane Curves
- Acceleration of Riged body (flyweight) with forces
- Trigo sin cos tan sec csc cot
- Concavity calculus
- Problem 126 explanation please
- Finding the sum of sequence
- Decimal Fractional Parts of Segment Dim's on Hypotenuses of Dissimilar Right Triangles
- Product of Areas of Three Dissimilar Right Triangles
- Area of Right Triangle Using Radius of Incircle
- The Formula for the Curve of a Trumpet Bell

We need to reaarange the differential equation so that it can be solved easily...

$$\left( x \csc\left( \frac{y}{x}\right) - y\right) dx + x dy = 0$$

$$x \csc\left( \frac{y}{x}\right)dx - ydx + xdy = 0$$

$$xdy = -x \csc\left( \frac{y}{x}\right)dx + ydx$$

Divide the terms of the differential equation by $x$, getting:

$$dy = - \csc\left( \frac{y}{x}\right)dx + \left( \frac{y}{x}\right)dx$$

Apparently this modified form of differential equation is a homogenous differential equation. So we let $v = \frac{y}{x}$, $y = vx$ and

$dy = vdx + xdv$. So we get:

$$dy = - \csc\left( \frac{y}{x}\right)dx + \left( \frac{y}{x}\right)dx$$

$$vdx + xdv = - \csc(v)dx + vdx$$

$$ xdv = - \csc(v)dx$$

$$\frac{dv}{-\csc(v)} = \frac{1}{x} dx$$

$$-sin(v)dv = \frac{1}{x} dx$$

The above differential equation is now a variable-separable type...so we get the integral of individual terms.

$$-sin(v)dv = \frac{1}{x} dx$$

$$\int -sin(v)dv = \int \frac{1}{x} dx$$

$$cos(v) + c_1 = ln(x) + c_2$$

$$cos(v) = ln(x) + c_2 - c_1$$

$$cos(v) = ln(x) + C$$

Now getting the $v$:

$$cos(v) = ln(x) + C$$

$$v = cos^{-1}(ln(x) + C)$$

The solution of the given differential equation $\left( x \csc\left( \frac{y}{x}\right) - y\right) dx + x dy = 0$ would be:

$$y = vx$$

$$y = (cos^{-1}(ln(x) + C))x$$

$$y = xcos^{-1}(ln(x) + C)$$

Alternate ways of answering it are encouraged....